Dramaturgy of Absence: Transnational theatre productions within the border and prison complexes - Sharifi, Azadeh (Peripeti, 2026)
Dette essay analyserer Date of Performance af Unread Archives i grænse- og fængselsmiljøer. I artiklen undersøges dramaturgi og poetik gennem fravær som et kunstnerisk dispositif. Formålet er at belyse transnationale produktioners kontekst og udfordringer. This essay analyzes Date of Performance by Unread Archives in border and prison contexts. It examines dramaturgy and poetics through absence as an artistic dispositif. The aim is to highlight the context and challenges of transnational productions.